Trade Analysis of Factors Affecting Sales of Retail Sukuk Series SR009 - Zaenudin, Zaenudin; Kurniawan, Arie; Darodjatun, M.A.S Sridjoko (SKeTsa Bisnis (e-jurnal), 2023)
English Version Retail Sukuk is one of the mechanisms carried out by the government in fulfilling APBN financing as well as an attractive investment instrument for the public. As an investment instrument, there is a need for research on the determinants of trade in the market. This study uses a quantitative method with the dependent variable trading volume SR09, while the independent variables are retail sukuk prices, deposit rates, sharia deposit profit sharing ratios, retail state bond prices, BI middle rate, inflation, BI 7-Day Repo Rate. . The data used are time-series secondary data for each variable from April 2017 to March 2020. After the data was processed using the SPSS 25 application, it was found that after the data was processed using the SPSS 25 application, the results were that Retail Sukuk Price SR009, Bank Deposit Interest Rate, BI Middle Rate, Negative Effect of Retail Sukuk Trading Volume SR09, Inflation (X6), and BI 7-Day Repo Rate (X7) on Ri Sukuk Trading Volume tel SR09. Meanwhile, the Sharia Banking Profit Sharing Ratio has a positive effect on the Trading Volume of Retail Sukuk SR09. The next result is that the seven variables simultaneously affect the dependent variable. Versi Indonesia Sukuk Ritel merupakan salah satu mekanisme yang dilakukan pemerintah dalam pemenuhan pembiayaan APBN sekaligus sebagai instrumen investasi yang menarik bagi masyarakat. Sebagai instrumen investasi, perlu adanya penelitian tentang faktor-faktor penentu perdagangan di pasar. Penelitian ini menggunakan metode kuantitatif dengan variabel dependen volume perdagangan SR09, sedangkan variabel independennya adalah harga sukuk ritel, suku bunga deposito, nisbah bagi hasil deposito syariah, harga obligasi negara ritel, kurs tengah BI, inflasi, BI 7-Day Repo Rate. . Data yang digunakan adalah data sekunder time-series masing-masing variabel dari bulan April 2017 sampai dengan Maret 2020. Setelah data diolah menggunakan aplikasi SPSS 25, didapatkan hasil bahwa Setelah data diolah menggunakan aplikasi SPSS 25 didapatkan hasil bahwa Harga Sukuk Ritel SR009, Suku Bunga Deposito Bank, Kurs Tengah BI, Pengaruh Negatif Volume Perdagangan Sukuk Ritel SR09, Inflasi (X6), dan BI 7-Day Repo Rate (X7) terhadap Volume Perdagangan Sukuk Ritel SR09. Sedangkan Rasio Bagi Hasil Perbankan Syariah berpengaruh positif terhadap Volume Perdagangan Sukuk Ritel SR09. Hasil selanjutnya adalah ketujuh variabel tersebut secara simultan berpengaruh terhadap variabel dependen.